Diseño e implementación del sistema de control y monitoreo para el proceso de potabilización del agua en el Centro de Generación Miravalles - Sancho-Salazar, Andrés (Instituto Tecnológico de Costa Rica, 2005)
Drinking water is a vital resource for the human being for the development of daily activities as much as for industrial works. The “Centro de Generación Miravalles” (CGM) has a small system for drinking water treatment, designed to supply the needs of human consumption, bathroom fittings, cleaning and air conditioning system. From the beginning the system was designed to work automatically using discrete technology through relays and contactors, however, part of the equipment suffered multiple damages during the later years since their construction in 1994. These problems forced to develop part of the process manually by skilled workers, which brought unnecessary operative and economic costs. This was developing an untrustable and inefficient drinking water treatment system. To solve this problem the CGM decided to restructure the process with the establishment of a new technology based on centralized automation using a PLC (Programmable Logic Controller) Allen Bradey SLC 500, with the possibility to make easy modifications or improvements. Furthermore, this technology enabled to incorporate the process to the predictive maintenance system installed in the CGM control center with Wonderware software tools. All of the process is monitored from a screen in the control center located in the main building of CGM. This screen shows important variables for the process in dynamic drawings, and has an alarm window that describes the problem and the moment it occurred. This is a valuable tool that allows focusing any problem occurring during the process and helps correct it faster.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2005.
Keywords: Dosificación; Agua potable; Hardware; Software; Control; Automatización